Tricalcium silicate-based cements: Properties and modifications - Duarte, Marco Antonio Hungaro; Marciano, Marina Angélica; Vivan, Rodrigo Ricci; Tanomaru Filho, Mario [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP]; Camilleri, Josette (FapUNIFESP (SciELO), 2018)
Mineral trioxide aggregate (MTA) has been widely used for different reparative procedures in endodontics. The extensive use of this cement for pulp capping, apexifications, apical surgeries, and revascularization is related to its ability to induce tissue repair and to stimulate mineralization. Several research studies have tested modifications in the composition of MTA-based cements in order to enhance their clinical performance. Novel formulations have been introduced in the market with the aim of increasing flowability. Important properties such as appropriate radiopacity and setting time, color stability, alkaline pH, release of calcium ions, and biocompatibility have to be considered in these new formulations. The latest research studies on the physical, chemical, and biological properties of tricalcium silicate-based cements are discussed in this critical review.
Keywords: Biocompatible materials; Dental materials; Endodontics; Root canal filling materials